ANALISIS JENIS DAN PENYEBAB KESALAHAN MAHASISWA DALAM SOAL PERSAMAAN DIFERENSIAL ORDE N - Sumargiyani, Sumargiyani (Program Studi Pendidikan Matematika, 2025)
This research aims to analyse the types of errors and causes of errors in solving n-order differential equation problems by students. This type of research is quantitative descriptive to describe the percentage of errors and qualitative descriptive to describe the causes of errors. The research will be carried out in the odd semester 2024/2025, involving 20 Mathematics Education students from Ahmad Dahlan University as research subjects. The instrument used was two questions in essay form and analysed using the error analysis stages according to Newman. The research results showed that students did not experience errors in reading the questions. The average error in understanding the questions reached 15%, while the error in transforming the questions was 8%. Errors in the completion process were 33%, while the highest errors occurred at the verification stage, namely 41%. Errors that occur are caused by students having difficulty in understanding the relationship between differential equations and their characteristic solutions, in factoring and determining real and complex roots, in determining general solutions, especially when they have twin roots, both real and complex, and selecting specific solutions and having difficulty compiling the final solution correctly.